Factors Affecting Students’ Intention in Adopting Takaful - Rashid, Nurul Nabilah Aminul; Hussin, Mohd Yahya Mohd; Hadi, Fatimah Salwa Abd; Razak, Azila Abdul; Romli, Nurhanani; Saad, Ram Al Jaffri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the relationships and effects between factors in the Theory of Planned Behaviour namely attitude, subjective norms and perceived behavioural control towards students’ intention in adopting Takaful. This study uses a questionnaire instrument involving 310 students from one university in Malaysia. To analyse the data, the Statistical Package for Social Science (SPSS) was used through Pearson Correlation coefficient and Multiple Linear Regression analysis. The findings revealed strong and positive relationship as well as significant effect between attitude, subjective norms and perceived behavioural control towards students’ intention to adopt Takaful. The implications of the study highlighted that attitude, subjective norms and perceived behavioural control have significant relationships and effects on the intention of students in UPSI to adopt Takaful in Malaysia. Thus, Takaful operators need to consider these factors in the future when they want to develop strategies to increase the number of their clients.